2013
DOI: 10.1016/j.pediatrneurol.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic and Ischemic Stroke in Children With Cancer

Abstract: BACKGROUND Adult survivors of childhood cancer have an increased risk of cerebrovascular disease; little is known about early stroke risk in childhood cancer. Our objectives were to assess stroke prevalence in children with cancer; to establish cancer and stroke type; and to determine if modifiable risk factors for stroke were present. METHODS Children with stroke and cancer were compared to all children seen for cancer at a single institution from 2000–2009. An international classification of disease-9th ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 31 publications
4
41
1
2
Order By: Relevance
“…It ranged from 0.47% to 4.2% in various studies. [18][19][20] Unlike the other studies, five cases of intracranial aspergillosis (n ¼ 5/23; 19.2%) occurred during induction and reinduction phases. Children were receiving intensive chemotherapy with corticosteroids and had severe neutropenia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It ranged from 0.47% to 4.2% in various studies. [18][19][20] Unlike the other studies, five cases of intracranial aspergillosis (n ¼ 5/23; 19.2%) occurred during induction and reinduction phases. Children were receiving intensive chemotherapy with corticosteroids and had severe neutropenia.…”
Section: Discussionmentioning
confidence: 98%
“…L-asparaginase treatment causes imbalance of pro-and anticoagulating systems. [15][16][17][18] The prevalence of intracranial thrombosis and hemorrhage in this cohort was 1.4% (n ¼ 5/343). It ranged from 0.47% to 4.2% in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoproliferative malignancies can also be associated with secondary immune thrombocytopenia (54). In a study by Correale et al (1990) on 989 patients with lymphoma, 2% had ICH, in clear association with platelet alterations (66) and in a 2013 study on pediatric cancer patients, all those suffering with ICH had platelet counts of <100,000/mm 3 (67).…”
Section: Pathophysiologymentioning
confidence: 99%
“…In comparison, a metaanalysis of 17 prospective studies comprising 1752 children with ALL estimated the rate of CNS thrombosis including cerebral infarction and stroke to be 2Á9% (Caruso et al, 2006) and a large British study with 1824 children with ALL reported an incidence of 1Á1% (Qureshi et al, 2010). A recent large American study on children with cancer and stroke reported two CSVTs in 190 children with ALL (1Á1%) (Noje et al, 2013) Thirteen (65%) of the children with CSVT were boys. One patient with CSVT had bilineage ALL, two patients had T-cell ALL while the others had precursor-B ALL.…”
Section: Cases Of Csvtmentioning
confidence: 99%